Графічний параметр української рими - Мовчун, Л. (Культура слова, 2020)
Стаття присвячена проблемі класифікації української рими за
графічно-акустичною ознакою. Традиційний розподіл рим на графічні
й акустичні не охоплює всього розмаїття способів і засобів фіксації
римових слів на письмі, зокрема в контексті сучасної поезії, автори
якої активно використовують вкраплення іншомовної графіки та
нелітерні знаки. Проаналізований матеріал дає підстави для поділу
рим на формально-акустичні, акустичні, акустично-графічні,
графічно-акустичні та формально-графічні. Уточнена класифікація
рим за графічно-акустичною ознакою дасть змогу вибудувати
осучаснену загальну систематику української рими. This study deals with the classification of Ukrainian rhymes based on
visual and phonic signs.
Ukrainian orthography is based on the phonemic principle, taking
into account morphological, traditional and differential. It is well adapted
to reproduce the consonance of words in a letter, so predominantly the
reader does not experience the feeling of splitting the image of the rhyme.
Despite the clarity of the concepts ‘visual’ and ‘phonic’, the terms ‘visual
rhyme’ and ‘phonic rhyme’ defined in the scientific literature differently.
Our purpose was to study the means of visual representation of
rhyming words and analyze the degree of coincidence of the visual images
of the rhyme components. Mainly the aesthetic intention is an impulse of
employing graphic techniques that estrange visual images of components
from each other or bind them on the basis of orthographic deviation. The
authors of modern poetry actively apply foreign letter inclusions, rows of
dots, figures and other non-alphabetic signs.
Analysed material gave grounds for the rhymes distribution to phonic,
formally phonic, phonic-and-visual, visual-and-phonic, formally visual. In
phonic rhymes, the relative parts of the rhyming words are not identical
in the letter. Formally phonic group includes rhymes with non-literal or
foreign-literal components. Phonic-and-visual rhymes takes into account
the cases of traditional notation of some letters. The vowels of these rhymes
are identical. Visual-and-phonic rhymes expect complete correspondence
between the vowels and the letters of the correlative parts of the rhyming
words. Formally visual rhymes cover cases of visual identity of correlated
parts of the rhyming words and dissimilarity of vowels.
A refined rhyme classification will help to originate a modernized
general systematics of Ukrainian rhymes.